Analysis of the Use of Augmented Reality (AR) in Digital Marketing Campaigns: A Case Study of a Fashion Brand - Nurhaliza (Journal of Digital Marketing and Search Engine Optimization, 2025)
The development of digital technology has driven changes in marketing strategies, with Augmented Reality (AR) becoming one of the key innovations to increase consumer engagement. The use of AR in video-based social media platforms such as TikTok opens up new opportunities for fashion brands to create more interactive and immersive marketing experiences. This study aims to analyze the effectiveness of using AR in a fashion brand's digital marketing campaign on TikTok and identify the factors that influence it. The method used is qualitative research with a case study approach, through in-depth interviews with TikTok users and observation of AR campaign content of fashion brands active on the platform. The results show that AR visual quality, content relevance to TikTok trends, ease of filter access, and the level of filter interactivity are key factors in increasing consumer engagement and purchase interest. In addition, the emotional and entertainment experience offered by AR contributes to positive brand perception. The conclusion of this study confirms that AR is not just a technology gimmick, but an effective experiential marketing strategy. The practical implications of this research provide guidance for brands in designing more creative and relevant AR-based campaigns, while its academic contributions enrich the literature review on immersive technology-based digital marketing. This research also opens up opportunities for further exploration in other industry sectors and other social media platforms.